Mammal diversity in the geothermal power plants, West Java, Indonesia - TEGUH HUSODO; ERRI NOVIAR MEGANTARA; INDRI WULANDARI; IRINA ANINDYA MUSTIKASARI; PUPUT FEBRIANTO; MUHAMMAD PAHLA PUJIANTO; NUGRAHA PUTRA MAULANA; YUANSAH YUANSAH (Smujo International, 2024)
Abstract. Husodo T, Megantara EN, Wulandari I, Mustikasari IA, Febrianto P, Pujianto MP, Maulana NP, Yuansah. 2024. Mammal diversity in the geothermal power plants, West Java, Indonesia. Nusantara Bioscience 16: 81-88. Geothermal energy is a critical renewable resource to address global energy demands. West Java, Indonesia, in particular, stands out with six geothermal power plants, including Kamojang, Gunung Salak, and Darajat Geothermal Power Plants. However, developing geothermal potential in biodiverse highland ecosystems raises concerns about its negative impact on biodiversity, especially mammals, making it essential to monitor and manage these areas for environmental sustainability. In 2019, a comprehensive study on mammal species was conducted in three geothermal power plants: Kamojang, Darajat, and Gunung Salak, all located in West Java, Indonesia. These geothermal power plants are located within diverse natural landscapes. The study employed various methods such as direct encounters, sign surveys, collapsible trapping, camera traps, and interviews with local communities. The mammal diversity study around the Kamojang, Darajat, and Gunung Salak Geothermal Power Plant areas revealed 32 mammal species from 18 families. Gunung Salak had the highest diversity with 22 species, primarily Sciuridae, primates, and some Carnivora species. Conversely, Kamojang had 20 species dominated by Muridae, and Darajat had 19 species with a similar dominance of Muridae, highlighting different characteristics among these geothermal power plant locations. Conservation status analysis identified species of high conservation concern, emphasizing the importance of preserving these habitats for biodiversity conservation.